Implementation of comprehensive emergency obstetric neonatal care (ponek) in Indonesia Hospitals: a literature review - Mulyono, Afieina Maulida; Umaroh, Ayu Khoirotul (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background: MMR and IMR in Indonesia are still high compared to the targets set by the government and SDGs. One way to address this is through the implementation of 24-hour PONEK. The implementation of PONEK is important to note because quality PONEK implementation can reduce MMR and IMR. This study purpose was to provide a more comprehensive understanding of the implementation of PONEK in hospitals Method: This type of research is a literature review using Google Scholar, PubMed, and Scopus databases with keywords implementasi OR pelaksanaan OR penerapan AND PONEK OR EmONC OR CEmONC. The inclusion criteria were the implementation of PONEK in Indonesia in all types of hospitals, using Indonesian and English, publication year range 2012-2022, original research. Results: The lack of health worker training was the main problem with PONEK program inputs. As for the PONEK program process, communication within the team was good and the implementation of monitoring and evaluation has gone well. As for the output of the PONEK program, there are no studies detailing the achievement of targets. Conclusion: The implementation of the PONEK program has been running, but there are still some things that have not been implemented properly. Further research is needed to evaluate the output of PONEK implementation.